KEPASTIAN HUKUM TEMPAT BERDAGANG BAGI PEDAGANG KAKI LIMA DI PASAR KLENDER JAKARTA TIMUR - Fahririn; Yuherman (Esensi Hukum, 2022)
Market activity cannot be separated from the interaction of traders and buyers which as buyers pass through the market area causing traffic disorder in the market area. Causing traffic jams in the market area so that it affects the orderliness of the roads around the market area. Another fact is that since the establishment of modern supermarkets, which are more organized and cleaner, the functions of traditional markets or people's markets are less than optimal. This study uses a field research type of research method, namely research that is directly related to the object under study to obtain information about the reality that exists in the field. The conclusion of this study is that the role of street vendors in creating public order and facilities needs to be reviewed because considering the large number of evictions that occur and are considered as a form of problem and are considered disturbing and even abusing public facilities. Suggestions from this research are street vendors at PD Pasar Jaya Klender, East Jakarta, do not get direct management and do not get legal certainty in accordance with existing policies in several regulations that directly regulate public order and facilities, including the management of street vendors.